Assessing preschoolers’ approaches to learning in the Chinese context: a scale for teacher-parent co-evaluation - Feng, Lina; Wang, Jingjing (Frontiers in Psychology, 2023)
Introduction An effective assessment of preschoolers’ approaches to learning (ATL) requires multiple-reporter co-evaluation, such as teachers and parents. Based on extant research on children’s ATL combined with Chinese cultural background and educational policies, this study aims to develop an ATL scale suitable for Chinese teachers and parents to co-evaluate preschoolers’ ATL. Methods Exploratory and confirmatory factor analysis (CFA) of the data collected from teachers (n=833) and parents (n=856) demonstrates the four-factor structure of the ATL: creativity, learning strategy, competence motivation, and attention/persistence, wherein creativity is a new dimension uncovered in the Chinese context. Results Psychometric analysis demonstrates that the scale has good reliability and validity. Multi-group CFA further shows that the measurement model is robust and independent from reporter identity. Discussion The current study contributes a novel and easy-to-use measurement instrument with 20 items for educational practitioners and for scholars who are interested in cross-cultural comparison or longitudinal development of Chinese children’s ATL.